PENERAPAN METODE SAW DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KINERJA PEGAWAI APARATUR SIPIL NEGARA - Gitarya, Leci; Sartika, Devi; Trianggana, Dimas Aulia (Smart Education, 2025)
Abstract: State Civil Servants are always required to have full loyalty and obedience in carrying out their duties. Decision support systems can be used as a solution to a problem or for an opportunity. The SAW method is a method that can help solve complex problems by structuring a hierarchy of criteria. Based on this research, the researcher tried to prove previous research and increase the accuracy of the data so that the researcher took the title